Description of Knowledge of Pregnant Women in Trimester III About the Impact of Fatimah Grass Consumption in the Mariana Clinic Medan City in 2021 - Hasnita Treesna Sandi Harefa; Debora Paninsari; Rahma Yani Nasution; Linda Mala Sari Harahap; Putri Damaiyanti (LLDIKTI Wilayah 1, 2021)
Fatimah grass (labisa pumila) in anastatica Greek or commonly referred to as the root of Fatimah or siti Fatimah, Fatimah's kancip which comes from the Arabian peninsula. Herbal remedies are considered safe because they come from natural products and have fewer side effects. Fatimah grass (Anastatica Hierochuntica) soaking water or commonly known as Rose Jericho is used as a medicine during pregnancy, especially before delivery, which is believed to be able to launch labor, reduce postpartum bleeding and treat the postpartum period. The researchers conducted a study with the aim of knowing the Knowledge Description of Third trimester Pregnant Women about the Impact of Fatimah Grass at the Mariana Clinic in 2021. The population in this study was 30 people. From the results of research based on age (20-29) about 53.3%, age (30-39) 40%, age (40-49) 6.6%, the majority of respondents have high school education / equivalent as many as 17 people (56.6% ), while the minority of respondents had junior high school education as many as 4 people (13,3%). The majority of respondents worked as housewives as many as 19 people (63.3%), while the minority of respondents worked as civil servants as many as 3 people (10%). Based on the conclusion, it can be concluded that the Knowledge Description of Third Trimester Pregnant Women About the Impact of Grass Consumption Fatimah is mostly less knowledgeable as many as 14 people (46.6 %), while the minority of respondents are knowledgeable enough as many as 7 people (23.3%).